Viral load and duration of BK polyomavirus viraemia determine renal graft fibrosis progression: histologic evaluation of late protocol biopsies - Reischig, Tomas; Kacer, Martin; Hes, Ondrej; Machova, Jana; Nemcova, Jana; Kormunda, Stanislav; Pivovarcikova, Kristyna; Bouda, Mirko (Nephrology, dialysis, transplantation, 2019)
BACKGROUND: Polyomavirus BK (BKV) infection of the renal allograft causes destructive tissue injury with inflammation and subsequent fibrosis. METHODS: Using a prospective cohort of patients after kidney transplantation performed between 2003 and 2012, we investigated the role of BKV viraemia in the development and progression of interstitial fibrosis and tubular atrophy (IFTA). The primary outcome was moderate-to-severe IFTA assessed by protocol biopsy at 36 months. RESULTS: A total of 207 consecutive recipients were enrolled. Of these, 57 (28%) developed BKV viraemia with 10 (5%) cases of polyomavirus-associated nephropathy (PVAN). Transient (<3 months) BKV viraemia occurred in 70% of patients, and persistent (≥3 months) BKV viraemia in 30%. A high viral load (≥10 000 copies/mL) was detected in 18% and a low viral load (<10 000 copies/mL) in 61%, while the viral load could not be determined in 21%. Moderate-to-severe IFTA was significantly increased in high [71%; odds ratio (OR) = 12.1; 95% confidence interval (CI) 1.62-90.0; P = 0.015] or persistent BKV viraemia (67%; OR = 6.33; 95% CI 1.19-33.7; P = 0.031) with corresponding rise in 'interstitial fibrosis + tubular atrophy' scores. Only patients with transient low BKV viraemia showed similar incidence and progression of IFTA to the no-BKV group. Persistent low BKV viraemia was uncommon yet the progression of fibrosis was significant. Only recipients with PVAN experienced inferior graft survival at 5 years. CONCLUSIONS: These data suggest that only transient low BKV viraemia does not negatively affect the progression of allograft fibrosis in contrast to excessive risk of severe fibrosis after high or persistent BKV viraemia.
Keywords: virová nálož; Polyomavirus Infections; Kidney Diseases; virus BK; Male; Graft Survival; replikace viru; progrese nemoci; viral load; BKV viraemia; fibrosis; fibróza; Transplantation, Homologous; BK Virus; Tumor Virus Infections; Prospective Studies; nemoci ledvin; mužské pohlaví; Disease Progression; Fibrosis; Viral Load; homologní transplantace; renal transplantation; lidé; polyomavirové infekce; Viremia; ženské pohlaví; Virus Replication; infekce onkogenními viry; transplantace ledvin; Humans; Kidney Transplantation; přežívání štěpu; viremie; Female; lidé středního věku; BK polyomavirus; Middle Aged; prospektivní studie